MULTIMODAL ANALYSIS OF TV COMMERCIALS IN TEACHING ADVERTISEMENT: STIMULATING STUDENTS’ CRITICAL THINKING - Ima Kusumastuti (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
Advertisement has a big influence in our life as it shows everywhere each day through magazines, newspapers, radio, and even television. The advertisers use writing, visual images, speech, or music to promote their product. The creative and persuasive use of the multimodality supports them to promote the product. One of the attractive targets to promote their product is teenagers which are identified as people ages 12 to 17. This makes the study of multimodality in advertisement for students, mainly TV commercials, becomes important to be conducted at school. Stimulating students’ critical thinking to become aware of persuasive strategies through multimodality in TV commercial is needed. This study is focusing on the analysis of multimodality namely language, visual image, and music illustration used in TV commercials and its use to stimulate the junior high school students’ critical thinking at English as Foreign Language (EFL) classroom. The implication of this research is to analyze TV commercials using Multimodal Analysis and its use in stimulating students’ critical thinking, to become aware of Advertisement’s persuasive intention to promote their product.